2001
DOI: 10.1172/jci10403
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor pathway inhibitor-2 is a novel inhibitor of matrix metalloproteinases with implications for atherosclerosis

Abstract: Degradation of ECM, particularly interstitial collagen, promotes plaque instability, rendering atheroma prone to rupture. Previous studies implicated matrix metalloproteinases (MMPs) in these processes, suggesting that dysregulated MMP activity, probably due to imbalance with endogenous inhibitors, promotes complications of atherosclerosis. We report here that the serine proteinase inhibitor tissue factor pathway inhibitor-2 (TFPI-2) can function as an MMP inhibitor. TFPI-2 diminished the ability of the inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
0
8

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(141 citation statements)
references
References 53 publications
3
130
0
8
Order By: Relevance
“…Our data may also indicate that other inhibitors of MMPs in the atherosclerotic lesion, such as TIMP-2, TIMP-3, and the tissue factor pathway inhibitor-2, 31 have a more essential role than TIMP-1 in the regulation of MMPs during plaque evolution. In addition, because TIMP-1 does not affect MMP-14 activity, it is possible that this proteinase could be critical in lesion remodeling through its ability to activate proMMP-2 and digest fibrillar collagens.…”
Section: Discussionmentioning
confidence: 74%
“…Our data may also indicate that other inhibitors of MMPs in the atherosclerotic lesion, such as TIMP-2, TIMP-3, and the tissue factor pathway inhibitor-2, 31 have a more essential role than TIMP-1 in the regulation of MMPs during plaque evolution. In addition, because TIMP-1 does not affect MMP-14 activity, it is possible that this proteinase could be critical in lesion remodeling through its ability to activate proMMP-2 and digest fibrillar collagens.…”
Section: Discussionmentioning
confidence: 74%
“…However, the domain also contains RGD-dependent and RGD-independent recognition sites for α V β 3 and α V β 5 integrins and can regulate angiogenesis through integrinmediated signalling (Pedchenko et al, 2003). Tissue factor pathway inhibitor-2, despite being a serine protease inhibitor, can also inhibit MMPs, including the gelatinases (Herman et al, 2001).…”
Section: Gelatinase Inhibitors Naturally Occuring Gelatinase Inhibitorsmentioning
confidence: 99%
“…TFPI-2 is thought to be involved in the coagulation cascade, 13 as well as the proliferation of smooth muscle cells 14 and inhibition of matrix metalloproteinase, 15 although the mechanism of action is still unclear. It was recently reported that TFPI-2 has unique functional properties to stimulate the growth of RPE cells without the growth stimulatory functions on fibroblasts and vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%